QUANTITATIVE ANALYSIS OF TECHNOLOGICAL DEVELOPMENT AND ITS IMPACT ON SOCIOECONOMIC GROWTH IN THE PHILIPPINES - Maria Ysabel Dela Cruz (JTH: Journal of Technology and Health, 2025)
This study investigates the impact of government investments in Information and Communication Technology (ICT) on digital inclusion and socioeconomic development in the Philippines. Despite increasing national attention to digital transformation, there remains limited quantitative evidence linking public ICT spending to tangible improvements in inclusive digital access and broader development outcomes. This study aims to fill that gap by providing a country-specific, data-driven analysis that evaluates both the economic and social dimensions of ICT policy effectiveness. Using a quantitative research design, secondary data from national and international sources were analyzed through multiple linear regression models. Key variables included public ICT investment, digital literacy rates, broadband access, GDP growth, employment rate, and income inequality (GINI index). The results indicate that government ICT investments significantly enhance digital inclusion, which in turn has a positive and statistically significant impact on GDP growth and employment, while contributing to the reduction of income inequality. These findings support the hypothesis that ICT policies, when properly designed and implemented, can drive inclusive economic growth. The study also reveals that digital inclusion acts as a mediating factor between technology infrastructure and socioeconomic outcomes. The novelty of this research lies in its integration of digital equity considerations with macroeconomic indicators within a single empirical framework, offering evidence-based insights for policy formulation. It contributes to the global discourse on digital development by demonstrating how national ICT strategies can be leveraged to promote both technological advancement and social equity.